Chronic effects of training and subsequent physical detraining on histology and morphometry of adipose tissue in adult Wistar rats - Alex de Souza; Gabriel de Moraes Siqueira; Anelize de Oliveira Campello Felix; Carlos Castilho de Barros; Luis Augusto Xavier Cruz; Rafael Bueno Orcy; Fabrício Boscolo del Vecchio (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The objective of the study was to analyze the effects of physical exercise and subsequent detraining on histological and morphometric parameters of white adipose tissue (WAT) and brown adipose tissue (BAT). Also investigated were insulin and glucose tolerance. It was an experimental study with three groups: continuous moderate-intensity training (CMIT), high-intensity interval training (HIIT), and a control group (CG). Three assessments were carried out: pre-intervention, after 8 weeks of training, and after 4 weeks of detraining. A generalized estimation equation was performed for (group x moment), with Bonferroni post-hoc for group and moment in the analysis of adipocyte area and weight. A one-way ANOVA was performed to analyze the decay rate and the area under the curve between groups. For the intragroup study, repeated measures ANOVA with Bonferroni post-hoc was performed. An increase was observed between T2 and T3 in the area of perilumbar adipose tissue (747.3 ± 28.4 µm2 vs. 853.0 ± 15.7 µm2, p ≤ 0.01) and perirenal (770.3 ± 11.4 µm2 vs. 830 .9 ± 18.6 µm2, p ≤ 0.01) regardless of the group, as well as an increase in the subscapular BAT area from T1 to T3 (419.9 ± 38.5 µm2 vs. 751.8 ± 27.5 µm2, p ≤ 0.001). The weights of perirenal, perilumbar, and subscapular brown adipose tissues were lower in HIIT and CMIT compared to the CG (p ≤ 0.001). It was observed that after detraining, the calculation of the decline in glycemia showed a statistically significant difference (F = 8.79; p = 0.005) between CG and HIIT (0.78 % vs. 1.82 %), with a higher average percentage for HIIT. It is concluded that 8 weeks of CMIT and HIIT are efficient for weight control and adipose tissue area; however, this control is lost after 4 weeks of detraining, and even after this period, HIIT showed better insulin sensitivity.